Mackenzie Blue - Wells, Tina, 1980- (HarperCollins, 2009)
At the beginning of seventh grade, Mackenzie is worried--her best friend has moved to France, someone steals her diary, she alienates her two new friends, and it looks like she has lost her chance to win the Teen Sing contest.